2020
DOI: 10.1038/s41598-020-75827-7
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Belief Network model to link sanitary inspection data to drinking water quality in a medium resource setting in rural Indonesia

Abstract: Assessing water quality and identifying the potential source of contamination, by Sanitary inspections (SI), are essential to improve household drinking water quality. However, no study link the water quality at a point of use (POU), household level or point of collection (POC), and associated SI data in a medium resource setting using a Bayesian Belief Network (BBN) model. We collected water samples and applied an adapted SI at 328 POU and 265 related POC from a rural area in East Sumba, Indonesia. Fecal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Second, we only assessed the HWT practice in this study and not the safe storage practice. Safe storage is needed to prevent recontamination of treated water (Mintz et al, 1995), and, indeed, in another study in the same area, it was found that there is a "moderate" chance of recontamination due to inappropriate water storage (Daniel et al, 2020a). This implies that even though households were categorized as regularly practicing HWT in this study, the drinking water quality may not be safe to drink.…”
Section: Discussionmentioning
confidence: 74%
“…Second, we only assessed the HWT practice in this study and not the safe storage practice. Safe storage is needed to prevent recontamination of treated water (Mintz et al, 1995), and, indeed, in another study in the same area, it was found that there is a "moderate" chance of recontamination due to inappropriate water storage (Daniel et al, 2020a). This implies that even though households were categorized as regularly practicing HWT in this study, the drinking water quality may not be safe to drink.…”
Section: Discussionmentioning
confidence: 74%
“…There are some studies on household hygiene conditions that can inspire the questions used to measure household hygiene conditions, e.g., by [12,13]. Questions or variables from the SI form for household drinking water can also be used since they measure hygiene practices related to drinking water; see, for example, the studies of [5,11,14]. One can then use the adapted SI forms to inform which hygiene aspects should be tackled, which can then improve the general household hygiene conditions.…”
Section: Of 15mentioning
confidence: 99%
“…One can then use the adapted SI forms to inform which hygiene aspects should be tackled, which can then improve the general household hygiene conditions. Some hygiene-related studies have been conducted in Indonesia, for example, on handwashing practices [15][16][17] and general household hygiene conditions [5,13]. There are is also evidence that household hygiene is associated with children's malnutrition in Indonesia [18,19].…”
Section: Of 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we noted that some information relevant to drinking water safety was not included in the revised household practices form, such as: the duration of water storage; the volume of water inside the final storage container; whether the respondents used the same container for collection, intermediate storage, and final storage; and the last time the final storage container was cleaned with soap [31,[39][40][41][42][43]. This information may be relevant, especially if the SI aims to suggest effective control measures to improve drinking water quality.…”
Section: Reflection Of the Revised Sanitary Inspection Formmentioning
confidence: 99%